Knowledge Related to Hygiene Food Management Sites - Edza Aria Wikurendra; Halimatus Sanila; Agus Aan Adriansyah; Sri Ita Tarigan (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2021)
Hygiene and food sanitation issues at the Port of Tanjung Perak Surabaya are essential issues. At Tanjung Perak Port, Surabaya, there is a place where food management is not feasible. This study aimed to determine the relationship between knowledge with food management hygiene in the Port of Tanjung Perak, Surabaya. The type of research used in this study is an analytic survey with a cross-sectional approach. This study's population was all food handlers in the buffer area, and in the perimeter area of Tanjung Perak Surabaya, there were 216 people. The research sample was taken by random cluster sampling with a sample size of 141 people. The data analysis used is a chi-square analysis. The results showed that almost all (89.4%) knowledge of food handlers was lacking, and the food management area's hygiene was almost entirely (92.9%) not feasible. Experience related to food hygiene management with a significance of 0.001 (<0.05). Knowledge related to hygiene in food management in Tanjung Perak Port, Surabaya. Suggestions that can be given are conducting training and increased supervision/inspection of food management sites.